2001
DOI: 10.1203/00006450-200110000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Hematocrit Correlates Well with Circulating Red Blood Cell Volume in Very Low Birth Weight Infants

Abstract: Although circulating red blood cell (RBC) volume is a better measure of total body oxygen delivering capacity than hematocrit (HCT), circulating RBC volume is more difficult to measure. Thus, the HCT is often used in RBC transfusion decisions. However, several previous studies of low birth weight infants have reported that the correlation between HCT and circulating RBC volume is poor. Using a robust nonradioactive method based on in vivo dilution of biotinylated RBC enumerated by flow cytometry, the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…The mean RCV in our patients, 35.7 ml/kg soon after birth and 21.6 ml/kg at 6 wk, is similar to the results previously reported for newborn infants (1,4,5,7,8,10,11).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The mean RCV in our patients, 35.7 ml/kg soon after birth and 21.6 ml/kg at 6 wk, is similar to the results previously reported for newborn infants (1,4,5,7,8,10,11).…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the use of radioactive substances for research in infants would be considered ethically unacceptable in the 21st century. Fortunately, biotin has been developed as a safe, nonradioactive RBC label for studies of RCV and RBC survival in infants (10,11,14,24,25), allowing continued research in this important area.…”
Section: Red Cell Volume Changes In Vlbw Infantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In anemia, a reduction of the Hb is usually accompanied by reduction in the RBC and HCT [44]. It was revealed that venous HCT values correlated highly with circulating RBC volume [46]. Under autologous experimental conditions, the presence of oxidative stressed erythrocytes in blood exacerbates cytokine production markedly and thus the activation status of human monocytes indicates a probable influence of oxidative stress in these children [47].…”
Section: Discussionmentioning
confidence: 99%
“…13 Use of this method for short-term and long-term RBC survival has been validated against 14 C-cyanate in sheep 14 (and unpublished data) and 51 Cr in adult human volunteers. 9 Briefly, the RBC wash solution was prepared by the addition of 4 mL of 50-percent dextrose (Baxter, Deerfield, IL), 20 mL of 8.4-percent sodium bicarbonate (American Reagent Laboratories, Shirley, NY), and 1 mL sodium phosphate (American Reagent Laboratories) to 1 L of 0.9-percent sodium chloride.…”
Section: Studies Using Biotinylated Rbcsmentioning
confidence: 95%